2016
DOI: 10.18632/oncotarget.8311
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 in myeloid-derived suppressor cells: an opportunity for cancer therapy

Abstract: Cancer progression is in part determined by interactions between cancer cells and stromal cells in the tumor microenvironment (TME). The identification of cytotoxic tumor-infiltrating lymphocytes has instigated research into immune stimulating cancer therapies. Although a promising direction, immunosuppressive mechanisms exerted at the TME hamper its success. Myeloid-derived suppressor cells (MDSCs) have come to the forefront as stromal cells that orchestrate the immunosuppressive TME. Consequently, this heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 202 publications
(219 reference statements)
0
29
0
Order By: Relevance
“…However, we did not observe a similar pathway in glioma‐associated MDSCs (Fig. b ) but found that the downregulation of PRKAR1A was related to STAT3 phosphorylation, which is an important molecular pathway involved in the accumulation, differentiation and functional regulation of MDSCs …”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe a similar pathway in glioma‐associated MDSCs (Fig. b ) but found that the downregulation of PRKAR1A was related to STAT3 phosphorylation, which is an important molecular pathway involved in the accumulation, differentiation and functional regulation of MDSCs …”
Section: Discussionmentioning
confidence: 99%
“…In human cancer patients and mouse tumor models, massive accumulation of MDSCs is a hallmark of tumor progression (1016). MDSCs are therefore key targets in cancer immunotherapy (1, 1721). …”
Section: Introductionmentioning
confidence: 99%
“…3,57 In addition, the STAT3 level largely dictates the recruitment, activation and immunosuppressive function of MDSCs in the TME. 58 In LCP-GMP group, the downregulation of p -STAT3 in tumors suppresses MDSCs and many pro-tumor genes such as survivin, Bcl-xL and c-Myc, leading to decreased tumor cell survival and proliferation. 23 c-Myc selectively regulates tumor-infiltrating MDSCs, 59 and c-Myc suppression correlated with the reduction of PD-L1 in tumors.…”
Section: Discussionmentioning
confidence: 99%